2022
DOI: 10.1007/s10120-022-01326-5
|View full text |Cite
|
Sign up to set email alerts
|

Survival trends in gastric cancer patients between 1987 and 2016: a population-based cohort study in Finland

Abstract: Background Gastric cancer is the fourth leading cause of cancer-related deaths globally. There is a paucity of national studies examining gastric cancer mortality in relation to treatment status. This study evaluated the survival trends in gastric adenocarcinoma and all gastric cancers stratified by treatment in Finland during 1987–2016. Methods This population-based, nationwide, retrospective cohort study included all gastric cancer patients registered in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…As patients' age at diagnosis is considered one of the independent factors affecting GC survival [2,7,8,12,[14][15][16], the prognosis of young and elderly patients with stomach cancer has been estimated and compared in various studies, although the results were inconsistent. Most of the investigations found no differences [13,21] or better outcomes [7,8,12,14,16,19], while only a few studies reported poorer survival rates for young patients [17,18]. Also, it has been observed that young patients' survival was worse due to individual characteristics and different tumor behaviors [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As patients' age at diagnosis is considered one of the independent factors affecting GC survival [2,7,8,12,[14][15][16], the prognosis of young and elderly patients with stomach cancer has been estimated and compared in various studies, although the results were inconsistent. Most of the investigations found no differences [13,21] or better outcomes [7,8,12,14,16,19], while only a few studies reported poorer survival rates for young patients [17,18]. Also, it has been observed that young patients' survival was worse due to individual characteristics and different tumor behaviors [8].…”
Section: Discussionmentioning
confidence: 99%
“…Important predictive factors for GC prognosis include tumor patterns at diagnosis and access to effective treatment [2,[7][8][9][10][11]. Significant patient characteristics that can affect GC survival include the patient's age at diagnosis [7,8,[12][13][14][15][16][17][18][19] and the presence of comorbidities [8,20,21]. Elderly patients with gastric cancer are generally recognized as having a worse long-term prognosis than younger patients [3,4,8,12,14,16], but controversies exist regarding the impact of age on cancer-specific mortality [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the 5-year survival rate in the cardiac GC group was significantly lower than that in the non-cardiac GC group ( 42 ). A cohort study from 1987-1991 to 2012-2016 found that among non-cardia adenocarcinoma patients who underwent surgery, five-year survival increased from 29% to 38%, while survival increased from 4% to 7% for those who underwent CT; In cardiac adenocarcinoma, five-year survival increased from 16% to 40% for patients undergoing surgery and from 0% to 5% for those undergoing CT ( 43 ). As can be seen from the nomogram, the low differentiation grades of the GAC were significantly associated with poorer survival, which was consistent with many previous studies.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Despite advances in the current management of GC, including radiation, chemotherapy, and surgery, the 5-year overall survival of patients with advanced GC remains below 30%. 4 , 5 Poor prognosis and high mortality in GC are closely related to lymph node metastasis, delayed diagnosis, and limited treatment options. 6 Therefore, the development of new prognostic markers is very helpful for early diagnosis and GC prognosis.…”
Section: Introductionmentioning
confidence: 99%